(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
Commodity stocks represent such a resource that fully ensures the uninterrupted operation of an enterprise. Commodity stocks, being an element of material reserves, allow the enterprise not only to carry out its commercial activities, but also provides an opportunity to realize commodity exchange operations in the consumer market. At present, there is a trend of growth in the period of turnover of inventory of the enterprise, which directly affects on the decline of the level of stocks, but in spite of this, commodity stocks play the main role in the process of providing the company with the opportunity to carry out its commercial activities. Summarizing the above, it is difficult to overestimate the relevance of this topic in modern conditions.